Determining Factors for Long Term Use of Gadget by Preschool Children - Wardatus Sholihah; Allenidekania Allenidekania; Nur Agustini; Rukmini Rukmini; Dwi Yuniar Ramadhani (Jurnal Keperawatan Indonesia, 2025)
In the digital era, preschoolers spent more time playing on their gadgets than with their peers. The excessive use of gadgets (including laptops, cellphones, tablets, and similar electronic devices) can have negative impacts on preschool-age children. This study analyzes the determining factors that influence the duration of gadget use in preschool children. The study used a correlational design with a cross-sectional approach involving 318 parents who were selected using cluster sampling. The results showed that there was a significant relationship between the duration of gadget use and the gender of the parents (p = 0.001), parental education (p = 0.035), family economic status (p = 0.018), educational media (p = 0.039), distraction media (p = 0.029), and psychosocial development (p = 0.001). The factors that most influence the duration of gadget use in children are family economic status with lower income adjusted odds ratio (AOR) (0.327) 95% CI (0.106–0.947), educational media is to add information AOR (0.367) 95% CI (0.183–-0.736), distraction media so that the child doesn't fuss AOR (0.392) 95% CI (0.203–0.758) and children do not have psychosocial disorders AOR (0.348), 95% CI (0.189–0.638). The results of the study can offer a basis for developing the latest nursing interventions in providing education and support to parents and children when using gadgets. Keywords: factors of gadget use, parents, preschool age   Abstrak Faktor Penentu Lama Penggunaan Gawai pada Anak Usia Prasekolah. Pada era digital, anak prasekolah lebih banyak menggunakan waktunya untuk bermain gawai daripada dengan teman sebayanya. Penggunaan gawai yang berlebihan (termasuk laptop, telepon genggam, tablet, dan alat elektronik sejenis) dapat memberikan dampak negatif terhadap anak-anak usia prasekolah. Penelitian ini bertujuan untuk menganalisis faktor penentu yang memengaruhi lamanya penggunaan gawai pada anak usia prasekolah. Desain penelitian korelasional dengan pendekatan cross-sectional dengan melibatkan 318 orang tua yang dipilih menggunakan cluster sampling. Hasil penelitian menunjukkan adanya hubungan yang signifikan antara lamanya penggunaan gawai dengan jenis kelamin orang tua (p value= 0,001), pendidikan orangtua (p = 0,035), status ekonomi keluarga (p = 0,018), media edukasi (p = 0,039), media distraksi (p = 0,029) dan perkembangan psikososial (p = 0,001). Faktor yang paling memengaruhi lama penggunaan gawai pada anak yaitu status ekonomi keluarga dengan penghasilan ≤ upah minimum kabubaten/kota AOR (0,327) CI 95% (0,106–0,947), sebagai media edukasi yaitu menambah informasi AOR (0,367) CI 95% (0,183–-0,736), sebagai media distraksi supaya anak tidak rewel AOR (0,392) CI 95% (0,203–0,758), dan anak yang tidak mengalami gangguan psikososial AOR (0,348), CI 95% (0,189–0,638). Hasil penelitian dapat digunakan sebagai dasar dalam menyusun intervensi keperawatan yang terbaru dalam memberikan edukasi dan pendampingan bagi orantua dan anak saat menggunakan gawai.  Kata Kunci: anak usia prasekolah, faktor penggunaan gawai, orang tua